2017
DOI: 10.1115/1.4036501
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Dispersion, Stability, and Waveform Invariance in Nonlinear Monoatomic and Diatomic Systems

Abstract: Recent studies have presented first-order multiple time scale approaches for exploring amplitudedependent plane-wave dispersion in weakly nonlinear chains and lattices characterized by cubic stiffness. These analyses have yet to assess solution stability, which requires an analysis incorporating damping. Furthermore, due to their first-order dependence, they make an implicit assumption that cubic stiffness influences dispersion shifts to a greater degree than quadratic stiffness, and they thus ignore quadratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Thus, at the first-order of perturbation, we assume that the localized excitation (boundary condition) is given by a time-harmonic displacement applied at j = 0 of the form: u e (τ ) = εû e (τ ) = ε(Û e e iω p τ +φ ep + εÛ e e iω s τ +φ es ). (11) where i is the imaginary unit, the primary frequency corresponds to the angular frequency of excitation, i.e.,ω p ≡¯ , ω s is the secondary frequency,Û e is the magnitude of the excitation, and φ e p and φ e s are, respectively, the phases of the primary and secondary harmonics. Note that the amplitude of the secondary harmonic is taken much smaller than the primary one.…”
Section: Semianalytical Analysis Of Quadratic Locally Resonant Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, at the first-order of perturbation, we assume that the localized excitation (boundary condition) is given by a time-harmonic displacement applied at j = 0 of the form: u e (τ ) = εû e (τ ) = ε(Û e e iω p τ +φ ep + εÛ e e iω s τ +φ es ). (11) where i is the imaginary unit, the primary frequency corresponds to the angular frequency of excitation, i.e.,ω p ≡¯ , ω s is the secondary frequency,Û e is the magnitude of the excitation, and φ e p and φ e s are, respectively, the phases of the primary and secondary harmonics. Note that the amplitude of the secondary harmonic is taken much smaller than the primary one.…”
Section: Semianalytical Analysis Of Quadratic Locally Resonant Mmentioning
confidence: 99%
“…In general, nonlinear interactions involve either cubic and/or quartic potentials, such as the famous Fermi-Pasta-Ulam-Tsingou (FPUT) problem [5,6], or more complex models such as the Hertz interaction law in granular materials [7][8][9][10]. Recent studies on FPUT-type phononic lattices focused mainly on weakly nonlinear interactions and the effect of nonlinearity on the dispersion relations [11][12][13][14][15][16]. In these papers, it was shown that nonlinearity induces amplitude-dependent dispersion and group velocity, i.e., demonstrating the tunability potential of nonlinear phononic structures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of great interest, the number of investigations carried out on the nonlinear dynamic behavior of locally resonant metamaterials exhibiting attenuation frequency ranges is quite limited in comparison with linear ones, also because of the conceptual and modelling difficulties 16 20 . Only few works investigated the energy transfer mechanisms induced by the nonlinear coupling between the resonator and the host medium.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of nonlinearity on the metamaterial response has raised attention as it would enable the design of tunable structures [1]. Nonlinearities may induce amplitude-dependent dispersion and group velocities, and also the propagation of emergent waveforms, such as solitons [27][28][29]. However, only a few papers in the literature have addressed the effect of nonlinearity on locally resonant metamaterials [30][31][32].…”
Section: Introductionmentioning
confidence: 99%